Efficacy, safety and tolerability of topical terbinafine nail solution in patients with mild‐to‐moderate toenail onychomycosis: results from three randomized studies using double‐blind vehicle‐controlled and open‐label active‐controlled designs. (20th December 2011) - Elewski, B.E.; Ghannoum, M.A.; Mayser, P.; Gupta, A.K.; Korting, H.‐C.; Shouey, R.J.; Baker, D.R.; Rich, P.A.; Ling, M.; Hugot, S.; Damaj, B.; Nyirady, J.; et al.
Abstract Background Terbinafine nail solution (TNS) was developed for the treatment of onychomycosis. Objective To assess the efficacy of TNS vs. vehicle and amorolfine 5% nail lacquer. Methods Subjects with mild‐to‐moderate toe onychomycosis (25% to ≤75% nail‐involvement, matrix uninvolved) were randomized to receive either TNS or vehicle in two double‐blind studies, and to TNS or amorolfine in an active‐controlled, open‐label study. Primary endpoint was complete cure (no residual clinical involvement and negative mycology) at week 52. Secondary endpoints were mycological cure (negative mycology defined as negative KOH microscopy and negative culture) and clinical effectiveness (≤10% residual‐involvement and negative mycology) at week 52. Results Complete cure was not different between TNS vs. vehicle and amorolfine. Mycological cure was higher with TNS vs. vehicle, as was clinical effectiveness with TNS vs. vehicle, and TNS and amorolfine were not different for secondary efficacy endpoints. Patients achieving mycological cure had a better clinical outcome, and efficacy was improved in subjects with milder disease. Post hoc analysis suggests that nail thickness is an important prognostic factor. Moreover, mycological cure may require 6 months of treatment regimen while complete cure and clinical effectiveness may be achievable only after 10 months. A simulation study suggests that longer treatment duration would have resulted in higher complete cure with TNS vs. vehicle. Study treatments were well‐tolerated. Conclusion Primary efficacy objectives were not met in the studies reported herein. Possible reasons for failure to achieve significant outcomes include insufficient length of treatment; stringency of primary endpoint and severity of nail involvement of study population.